Fatigue life evaluation model for high-strength steel wire considering different levels of corrosion. Issue 3 (25th November 2022) - Bai, Nani; Li, Hui; Ma, Junming; Lan, Chengming; Spencer, Billie F.
Abstract: This article studies the quantitative influences of corrosion on the fatigue life of high-strength steel wires, considering a wide variation in the degree of corrosion. A multiparameter Weibull model for corrosion-stress-life (C-S-N) is proposed, and the Goodman relation is employed to deal with the dependences of stress ranges on positive stress ratios. Fatigue data are collected from the literature for three groups with different ultimate tensile strengths and the degree of corrosion ranging from 0.18% to 18.67%. This data is then used to estimate the parameters of the Weibull model; subsequently, quantitative influences of corrosion on fatigue life for steel wires with a wide range in the degree of corrosion are illustrated and discussed. The results indicate that the influence of ultimate tensile strengths on fatigue life for corroded steel wire can be ignored, because corrosion causes crack nucleation faster, especially at lower stress ranges. The fatigue life decreases sharply as the corrosion increases, and reduction is much pronounced under a lower stress range. Negative correlation of fatigue life and corrosion increases as the stress range decreases, which further confirms that corrosion has a higher influence at lower stress ranges. The proposed model can provide quantitative evaluation on the fatigue life of steel wires at specified survival probabilities, considering a wide range in the degree of corrosion; these results can be used by engineering designers to ensure the safety for cable-supported bridges during their lifetime.